Three-wave cross-lagged model on the correlations between critical thinking skills, self-directed learning competency and AI-assisted writing - Shen, Xiaolei; Teng, Mark Feng (Elsevier, 2024)
The impact of Artificial Intelligence (AI) on English writing is gaining prominence. This study aimed to examine the interplay between critical thinking skills, self-directed learning competency, and Artificial Intelligence writing by cross-lagged model, with the focus on the moderating role of self-directed learning competency on critical thinking skills and Artificial Intelligence writing. A total of 204 participants completed a critical thinking test, self-directed learning questionnaire and a writing task. The results revealed significant correlations between critical thinking skills, self-directed learning competence, and AI-assisted writing. However, the temporal correlations between critical thinking skills and self-directed learning exhibited a reciprocal pattern over three times, while the correlations between critical thinking skills, self-directed learning, and AI-assisted writing were unidirectional. Interestingly, the findings indicated that self-directed learning moderated the relationship between critical thinking skills and AI-assisted writing over two times, but not in the third time. These findings emphasized the pivotal roles of critical thinking skills and self-directed learning in AI-assisted writing among EFL learners. They also suggested that using AI-assisted tools critically and independently in writing can mitigate the tendency to over-rely on these tools.